Role of the Physical Therapist in Cystic Fibrosis Care. Issue 1 (4th October 2022) - Stanford, Gemma; Daniels, Tracey; Brown, Catherine; Ferguson, Katie; Prasad, Ammani; Agent, Penny; Gates, Alison; Morrison, Lisa
Abstract: In looking back on 2020 and 2021, this Perspective reflects on the monumental impacts of the rollout of cystic fibrosis (CF) transmembrane conductance regulator highly effective modulator therapies and the COVID-19 pandemic on the management of CF. Advancements in the clinical management of people with CF have been both enormous and rapid, and physical therapists specializing in the care of people with CF have been at the forefront of driving this evolution in care. This year sees the 30th anniversary of the UK Association of Chartered Physiotherapists in Cystic Fibrosis and, as is inevitable in reaching such milestones, thoughts have turned to origins, role, impacts, and the future. With the changing demographics of the population of people with CF after the introduction of highly effective modulator therapies, potentially with fewer secondary complications, the future role of the physical therapist who specializes in CF is in question. This Perspective reflects on and highlights the role of physical therapy within CF and provides insights into how physical therapists and respiratory therapists can evolve their roles to ensure relevance for the future.